Gaetano Mosca And The Rulling Class Analysis of Elite Group Domination in the Government System in Indonesia - Hamat, Yulianus Evantus; Pandor, Pius; Darus, Yulius; Nasar, Yulianus Lihong (Master Program of Sociology, Universitas Malikussaleh,, 2024)
The main focus of this article is to analyze the role and dominance of elites in the government system in Indonesia in the light of Gaetano Mosca's concept of the